Examining Race & Racism in the University: A Class Project - Vess, Lora E (Radical Teacher, 2016)
The rise of black consciousness through “Black Lives Matter” protests and recent events regarding police shootings of unarmed people of color have triggered a national dialogue on race, privilege, and discrimination. I structured my 400-level Race and Ethnicity course to build on the momentum of these conversations by incorporating a student-led race-centric research project whereby students learn and apply in-depth interview skills. Through this qualitative group project, students interviewed 31 members of the university community to investigate colorblindness, racial identity, privilege, racialized experiences, and institutional racism on their campus. In this article, I describe the project, and consider its strengths and limitations as a means of student learning about race, privilege, and discrimination in the U.S. today. I include student quotations gathered through final reflection papers to give voice to their experiences as well as a self-reflection of my experiences as part of this project, particularly as a white woman.